PERTUMBUHAN DAN PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA PENAMBAHAN DUA SUMBER NUTRISI - Afina Shifriyah; Kaswan Badami; Sinar Suryawati (Universitas Trunojoyo Madura, 2012)
White oyster mushroom (Pleurotus ostreatus) harvest tend to reduced because of nutrients decreasing in the growth media. An effort to increase its production is by adding nutrients into the growth media. This research aims to determine the effect of nutrition on growth and production of white oyster mushrooms. The nutrients used in this study is monosodium glutamate (MSG) and old coconut water. The research method used was Complete Randomized Design (CRD) analysis of variance with orthogonal contrasts. The treatments tested is the addition of nutrients after 3 times the harvest consists of four levels: control (without giving nutrient solution), the provision of nutrient solution Monosodium glutamate (MSG) 0.4%, 30% old coconut water and nutrient combination of MSG and old coconut water. The results show that the addition of nutrients was not significantly different to the parameters of the total fresh weight, total weight, mean stalk length, average diameter of the bodies and biological efficiency of fruit. However, it significantly different to the parameters of maximum hood width average and buds appearance time. Based on these observations we can conclude that feeding monosodium glutamate, old coconut water and combination of nutrients monosodium glutamate and old coconut water significantly affect to maximum hood width average and buds appearance time. Nutrition as well as without being given nutrients (control) of body fresh weight. Nutrition old coconut water is better than Monosodium glutamate to maximum hood width average. Monosodium glutamate or old coconut water nutrition is better than the combination of nutrients monosodium glutamate and old coconut water to the long shoots appear. Nutrition increase wet weight up to 1.89%.